2019
DOI: 10.1016/j.solmat.2019.110151
|View full text |Cite
|
Sign up to set email alerts
|

Impact of P3HT materials properties and layer architecture on OPV device stability

Abstract: We report a cooperative study conducted between different laboratories to investigate organic solar cell degradation with respect to P3HT material properties and different solar cell architectures. Various batches of P3HT were collected from different suppliers reflecting commercial availability as well as properties variability. Among the materials properties explicitly considered were the molar mass, dispersity, regio-regularity, impurities by trace metals and intrinsic doping evaluated from radical concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 98 publications
(130 reference statements)
1
14
0
Order By: Relevance
“…11 To further improve the efficiency as well as stability, the development of new material as light-harvesting, improvement in the device processing, and designing a stable device architecture are most essential. [81][82][83][84][85][86][87][88] Besides, interface engineering through CIL plays a significant role in the improvement of OSCs devices. Recently, it has been demonstrated that interface engineering, primarily through inserting CIL between the electrode and photoactive layer could significantly enhance the performance of OSCs.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 To further improve the efficiency as well as stability, the development of new material as light-harvesting, improvement in the device processing, and designing a stable device architecture are most essential. [81][82][83][84][85][86][87][88] Besides, interface engineering through CIL plays a significant role in the improvement of OSCs devices. Recently, it has been demonstrated that interface engineering, primarily through inserting CIL between the electrode and photoactive layer could significantly enhance the performance of OSCs.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…To date, PCE has exceeded over 18% in single‐junction NF‐OSCs 11 . To further improve the efficiency as well as stability, the development of new material as light‐harvesting, improvement in the device processing, and designing a stable device architecture are most essential 81–88 . Besides, interface engineering through CIL plays a significant role in the improvement of OSCs devices.…”
Section: Cathode Interlayer Materialsmentioning
confidence: 99%
“…21 There are several mechanisms of degradation that have been identified to have significant influence on the lifetime of OPVs. These include thermal, 22,23 oxygen and moisture, 24,25 UV radiance 26,27 and mechanical 9,28,29 degradation. These factors are responsible for two significant decay trends of PCE: burn-in and linear degradation.…”
Section: Introductionmentioning
confidence: 99%
“…We choose the well-studied blend of the donor P3HT and the acceptor phenyl-C61-butyric acid methyl ester (PC 60 BM) as the photoactive BHJ. [8,41] On top of this active layer, a P3HT DBL is deposited to decrease the electron injection from the anode into the lowest unoccupied molecular orbital (LUMO) of PC 60 BM due to the higher energetic barrier (see also Figure S1 in the Supporting Information). The DBL deposition is carried out by the digital and contactless AJP technique, which has recently experienced considerable attention in printed electronics research.…”
Section: Introductionmentioning
confidence: 99%